Infertility Caused by Inefficient Apoptotic Germ Cell Clearance in Xkr8-Deficient Male Mice - Yamashita, Yahiro (Mol Cell Biol, 2020)
During spermatogenesis, up to 75% of germ cells in the testes undergo apoptosis and are cleared by Sertoli cells. X-linked XK blood group-related 8 (Xkr8) is a plasma membrane protein that scrambles phospholipids in response to apoptotic signals, exposing phosphatidylserine (PtdSer). Here, we found that Xkr8(−/−) male mice were infertile due to reduced sperm counts in their epididymides. Apoptotic stimuli could not induce PtdSer exposure in Xkr8(−/−) germ cells. Consistent with the hypothesis that PtdSer functions as an “eat-me” signal to phagocytes, cells expressing phosphatidylserine receptor TIM4 and MER tyrosine kinase receptor efficiently engulfed apoptotic wild-type male germ cells but not Xkr8(−/−) germ cells. Fluorescence and electron microscopy revealed Sertoli cells carrying engulfed and degenerated dead cells. However, many unengulfed apoptotic cells and residual bodies and much cell debris were present in Xkr8(−/−) testes and epididymides. These results indicate that Xkr8-mediated PtdSer exposure is essential for the clearance of apoptotic germ cells by Sertoli cells. There was no apparent inflammation in Xkr8(−/−) testes, suggesting that the unengulfed apoptotic cells may have undergone secondary necrosis, releasing noxious materials that affected the germ cells. Alternatively, failure to engulf the apoptotic germ cells may have caused the Sertoli cells to starve and lose their ability to support spermatogenesis.